Percepção materna das habilidades empáticas dos filhos/as com desenvolvimento típico e filhos/as com transtorno do espectro autista - Souza, Edizângela de Fátima Cruz de (2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder whose main characteristics are impairments in social interaction and communication, and stereotypical patterns of behavior. Social deficits related to ASD have been associated with difficulties in empathic expression; however, results in this area are still inconclusive. It is believed that exploring empathy in ASD is crucial to understanding effective interventions aimed at developing social and emotional skills. In this sense, the objective of this dissertation was to compare the perception of mothers about the empathy of their children, children and adolescents, considering mothers who have children with ASD and mothers who have children with typical development (TD). To this end, three articles were prepared. The first aimed to carry out a systematic survey of the levels and types of empathy in children and adolescents with ASD and typical development. In this article, 26 studies were selected in the final sample, which were analyzed in eight categories: (1) Global empathy; (2) Cognitive and affective empathy; (3) Affective empathy; (4) Taking the perspective of others and theory of mind; (5) Emotion recognition; (6) Empathy and mental organization; (7) Empathy and alexithymia; and (8) Empathy processing. The second article aimed to analyze and adapt the psychometric indicators of the Interpersonal Reactivity Index – version for caregivers. Three empathy experts and 34 mothers participated in the content validity analysis (Age = 38.71 years; SD = 8.20). Both in the analysis of the judges and the target population, most of the items in the new scale presented adequate CVC values (>0.80), demonstrating evidence of content validity. To analyze the psychometric indicators, 260 caregivers participated (Age = 43.51; SD = 13.24). From this sample, 59 mothers (Mage = 34.61; SD = 7.13) of children aged 4 to 11 years were selected for divergent validity. The analysis of psychometric indicators showed that the original four-factor model is the most suitable for the scale. Evidence of validity was also found in relation to external measures, reliability (α= 0.94) and internal consistency (ω =0.93). Finally, the third article included 104 mothers of autistic children and adolescents with typical development (Age = 40.85; SD = 8.32), divided into two groups: 52 mothers of children with typical development and 52 mothers of children with ASD. These participants completed the Interpersonal Reactivity Index – version for caregivers. The results of the Multivariate Analysis of Variance (MANOVA) and post-hoc tests demonstrated significant differences: mothers of children with typical development perceived more empathic consideration and perspective taking in their children than mothers of children those with ASD. Analyzes with other variables showed that: mothers of girls perceived more empathic consideration and perspective taking in their daughters than mothers of boys; and mothers of autistic children and adolescents without comorbidities perceived more perspective taking in their children than mothers of autistic children and adolescents with comorbidities; It is understood that this study may contribute to understanding the empathy of autistic children and adolescents with typical development, in the perception of their mothers, and may support new studies that seek to deepen the topic, as well as interventions aimed at developing empathy in this public.